Laparoscopic cholecystectomy during COVID-19 pandemic- Retrospective analysis of tertiary care centre - Laudari, Uttam; Pradhan, Rosi; Shrestha, Dibesh; Timilsina, Bibek; Sapkota, Suhail; Karki, Dimindra; Lamichhane, Suraj; Parajuli, Anuj (Nepal Mediciti Medical Journal, 2021)
INTRODUCTION: Laparoscopic cholecystectomy is the most commonly performed general surgical procedure. During the COVID-19 pandemic, general recommendation worldwide is to postpone elective surgeries as far as possible to decrease the resource utilization and also aerosol-related transmission among hospital staff and patients. We conducted this study to see the burden of gallbladder disease, their management and outcomes of all patients who presented to our centre during first wave of COVID-19 pandemic.METHODS: We conducted a retrospective analysis of all patients who underwent laparoscopic cholecystectomy at the Hospital for Advanced Medicine and Surgery (HAMS) after the commencement of strict lockdown in the first wave of the COVID-19 pandemic. Ethical approval for the study was taken from Nepal Health Research Council. All the surgeries were performed as per HAMS interim policy for infection prevention and control during the COVID-19 pandemic. Data were extracted from the discharge sheet and outcomes in terms of duration of hospitalization, morbidity, mortality, and COVID -19 infection among patient and operating team staff after surgery were assessed.RESULTS: Out of 110 cases operated for gallbladder disease, 90 patients were included in the study with complete data. The most common presentations were dyspepsia (28) and biliary colic (22). Patients were managed with laparoscopic cholecystectomy (79), percutaneous cholecystostomy (4), laparoscopic subtotal cholecystectomy (5), open cholecystectomy (1). The median duration of hospitalization 22 hours. There was no COVID-19 transmission among staff and patients.CONCLUSIONS: Laparoscopic cholecystectomies are feasible during COVID-19 pandemic and safely performed following infection prevention guidelines. It can be still be performed in day case basis to decrease the bed occupancy and avoiding crowd in hospitals.